The Construction of Children’s Religiousity Character in The Digital Era Through Qur’anic Education Center of Asshaulatiyyah in The Sasak Society (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2026)
The digital era has brought significant changes to public life, particularly regarding the behavior and morals of the younger generation. The advancement of information and communication technology, especially social media, has become an inseparable part of students' lives, while simultaneously presenting new challenges for Islamic educational institutions in fulfilling their character-building role. This study aims to examine the role of educators and the strategies implemented in shaping students' character in the digital age, evaluate the obstacles faced in confronting contemporary challenges, and provide solutions for character development. This research employs a descriptive qualitative approach to explore the phenomenon deeply and contextually, utilizing data obtained from primary and secondary sources through three data collection techniques: semi-structured interviews with teachers and students (santri), non-participatory observation of daily religious activities, and a documentation study of the TPQ work program. The results indicate that character building cannot rely solely on theory but rather requires a strong synergy among three main pillars: families for supervision and habituation at home, educators as digitally literate facilitators, and society as a supportive environment. As a practical solution to these challenges, TPQ Asshaulatiyah implements five tactical steps, namely varying learning methods to be more interactive, implementing a positive reward and punishment system, fostering active communication with parents, applying an exemplary approach (uswah hasanah) by teachers, and establishing repetitive daily moral habituation through gentle personal corrections.
Keywords: religious character development; digital eras; Islamic education; Qur'anic education centers; character education; moral habituations